ASSESING STUDENT PERPECTIVES : A SURVEY OF TEXTBOOK EVALUATION AMONG SOPHOMORE ENGLISH EDUCATION STUDENTS - Syahid, Abdul; Syamsyara , Amaliya; Niesrina , Maulida Zahrotun; Fitrian , Novia; Saumi , Rahma Ibtida; Wulandari , Widya (Asosiasi Dosen Muda Indonesia, 2024)
This study contains the evaluation of the textbook